Household Strategy of Fishermen Facing Poverty in Teluk Kabung Selatan Bungus Teluk Kabung District West Sumatra Province - Harvita Haryenda; Darwis Darwis; Firman Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract This research aims to know the conditions of fishermen and the fishing household strategy in the face of poverty. This research was carried out in April 2017 which is located in Teluk Kabung Selatan Bungus Teluk Kabung District of West Sumatra Province. The methods used in this research is a survey method with the total number of respondents as many as 30 people and the determination of the respondents conducted in simple random sampling. The condition of the fishing households experiencing poverty can be seen from the large amount of dependent families, home ownership status, the amount of expenditure that is greater than the amount of income received, and factors causing poverty that isfishing technology still traditional by using the machine ships with robin 5 Power Horse, owes the habit and isolate area geographically causes high costs incurred to make ends meet. Strategies used by fishermen in the face of poverty is by optimizing the labor of family members such as spouses and children, diversified jobs such as working on the peasants, workers and interisland transport service providers, as well as utilize loans to relatives in the family or neighbors. Keywords: household condition, strategy, fisherman, poverty, Teluk Kabung Selatan.